ANALISIS CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN PT PELABUHAN INDONESIA IV (PERSERO) MAKASSAR - Muh Fuad Randy (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
Business competition is getting tighter, so many companies must be able to know and fulfill the wants or needs of their customers precisely. The level of competition is so tight that many companies no longer focus their marketing activities solely on finding new buyers / customers, but on how to maintain and increase customer loyalty. The strategy that is able to bridge between customers and companies, especially in terms of satisfaction and loyalty, is to apply a concept called Customer Relationship Management (CRM). This study aims to determine the effect of CRM both on satisfaction and loyalty partially and to know the indirect effect of CRM on loyalty through customer satisfaction as an intervening variable by drawing a sample of 60 people or customers. Based on the results of testing the coefficient of determination, it is known that the effect of CRM on customer satisfaction is 20.5% and the remaining 79.5% is influenced by other variables which are not addressed in this study. While the test results of the coefficient of determination in the second regression equation show that the CRM variable and customer satisfaction affect the level of customer loyalty by 44.8% and the remaining 55.2% is influenced by other variables which are not raised in this study. However, from the results of testing the intervening variable that customer satisfaction is not an intervening variable between CRM and customer loyalty.